(untitled) (OODBODHAN, 2025)
This study assesses the performance of M30 grade concrete incorporating Recycled Coarse Aggregate (RCA) sourced from Prithvi Rajmarga as a partial replacement for Natural Coarse Aggregate (NCA). RCA was manually processed and used to replace NCA at 0%, 10%, 20%, 30%, and 40% by weight. A control mix was designed with a constant water-cement ratio of 0.38 and a mix proportion of 1:1.94:3.22 (C:S:A). Comparative analysis revealed that RCA exhibited lower specific gravity and higher water absorption than NCA. Incorporation of RCA led to reductions in slump and fresh density. The 28-day compressive strength values were 38.69 MPa, 35.33 MPa, 34.70 MPa, 34.26 MPa, and 32.07 MPa for 0% to 40% RCA replacement levels, respectively. Compressive strength remained above the target threshold (fck + 4 = 34 MPa) up to 30% replacement. A similar declining trend was observed in flexural strength, with recorded values of 6.4 MPa, 5.98 MPa, 4.98 MPa, 4.52 MPa, and 4.04 MPa. The results indicate that RCA can replace NCA up to 30% without significantly compromising structural performance. This supports the potential of RCA in sustainable construction and contributes to effective construction and demolition waste management strategies.